PENGARUH KERJA TIM DAN ORGANIZATIONAL LEARNING TERHADAP KINERJA PEGAWAI BADAN DIKLAT PROVINSI KALIMANTAN BARAT - Lidya Natalia Sartono (Jurnal Manajemen Pendidikan, 2014)
The objective of the research is to obtain information about the effect of teamwork an organizational learning on job performance of employee at Education and Training Board at Province of West Borneo. The research was conducted by using quantitative survey method with path analysis applied in testing hypothesis. The number 71 employee as sample was selected by using Slovin formula. The research conclude: (1) there is direct effect of teamwork on job performance. (2) there is direct effect organizational learning on job performance. (3) There is direct effect teamwork on organizational learning. Therefore to enhance employee’s job performance can be carried out by teamwork and organizational learning.